(untitled) (GAIMS Journal of Medical Sciences, 2024)
Background: To examine visual outcome and vision related quality of life after Implantable Collamer Lens for Moderate to High Myopia and Myopic Astigmatism. Material and methods: A hospital-based prospective, interventional, observational study has been carried out to evaluate functional outcomes and patient satisfaction following phakic ICL implantation for the treatment of myopia and myopic astigmatism. In this study, we included 44 eyes of 26 patients, 15 females (58%) and 11 males (42%), mean age 24.56 ± 4.98 years (range: 18-35) with preoperative myopia (mean ± standard deviation [SD] refraction spherical equivalent, -11.485 ± 4.78 D). To investigate the effects of ICL implantation, we had compared between two groups: one group before surgery and another group one month after surgery. Measurements including uncorrected distance visual acuity (UCVA), corrected distance visual acuity (CDVA), spherical equivalent (SE) of manifest refraction, and corneal topography were obtained for all participants. The Quality-of-Life Impact of Refractive Correction (QIRC) questionnaire was administered to compare VRQOL between before and after ICL implantation. Results: The postoperative mean UCVA demonstrated a significant statistical improvement (p<0.001) from pre operative data, increasing from 0.04 ± 0.035 to 0.87 ± 0.23 (decimal acuity). The preoperative BCVA 0.85± 0.23 versus the mean postoperative BCVA 1.0 ± 0.18. The mean ± standard deviation of the preoperative refraction spherical equivalent was -11.485 ± 4.78 D. After surgery, this value decreased to -0.87 ± 0.40 D, demonstrating a statistically significant improvement (p<0.05). After surgical procedures, the QIRC scores were significantly higher (postoperative QIRC score: 53.84±7.14; P<0.001) versus preoperative QIRC score [mean ± SD], 43.68±5.69, with significant increases (P<0.001) for 14 of the 19 items. After ICL surgery, the group’s scores on items concerning convenience, well-being, and health problems were much higher than they were prior to the surgery. Despite the fact that nine patients (34%) encountered more concerns of night vision after surgery (mostly nonspecific glare and halo or arc effects), overall patient satisfaction was excellent, with 88% reporting that they were either satisfied or very satisfied with the surgical outcomes. Overall, none of the patients reported dissatisfaction. Conclusion: Implantation of an ICL for moderate to high myopia and myopic astigmatism resulted in both significant improvements in visual acuity and a substantial enhancement in vision-related quality of life (VRQOL) for the subjects. This suggests that ICL implantation can be a successful treatment option for these patients, leading to improved vision and a greater enjoyment of daily activities.